THE TECHNOLOGY OF AWAKENING THE MOTIVATION OF INTEREST IN KNOWLEDGE IN CHILDREN OF JUNIOR SCHOOL AGE (American Journal of Pedagogical and Educational Research, 2023)
The article reveals the specifics of achieving educational achievements based on the formation of positive motivation of students for educational activities. Theoretical and practical views on the motives of learning in the educational process are expressed.